Antioxidant Activity of Hydrolysates Prepared from Flaxseed Cake Proteins Using Pancreatin - Karamać Magdalena; Kulczyk Anna; Sulewska Katarzyna (Polish Journal of Food and Nutrition Sciences)
Proteins were isolated from defatted flaxseed cake and hydrolysed with pancreatin. The hydrolysis process was conducted at a stable temperature of 50°C and pH 7.5, and monitored with the pH-stat method. The obtained hydrolysates with a degree of hydrolysis (DH) of 5, 10, 15, 20, 25% were investigated in terms of antioxidant properties. The radical scavenging activity was assayed against DPPH· and ABTS·+, the reducing ability - with FRAP assay, and the capability to bind Fe(II) - by reaction with ferrozine. SE-HPLC analysis was used to determine molecular weight distribution of hydrolysis products.